Could the classical relativistic electron be a strange attractor?. Issue 1 (18th May 2004) - Horwitz, L. P.; Katz, N.; Oron, O.
Abstract : We review the formulation of the problem of the electromagnetic self-interaction of a relativistic charged particle in the framework of the manifestly covariant classical mechanics of Stueckelberg, Horwitz, and Piron. The gauge fields of this theory, in general, cause the mass of the particle to change. We show that the nonlinear Lorentz force equation for the self-interaction resulting from the expansion of Green's function has chaotic solutions. We study the autonomous equation for the off-shell particle mass here, for which the effective charged particle mass achieves a macroscopic average value determined by what appears to be a strange attractor.